(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
The article discusses the hadiths used in Ahmad Yugnaki’s epic poem “Hibat ul-haqoyiq”, the ways and methods of incorporating hadiths into the text, the text and its translation. The ideas are based on poetic fragments taken from the poet’s epic poem “Hibat ul-haqoyiq”.